2001
DOI: 10.2466/pr0.2001.88.2.527
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Symptoms in Refugees: Assessments with the Harvard Trauma Questionnaire and the Hopkins Symptom Checklist–25 in Different Languages

Abstract: The original versions of the Harvard Trauma Questionnaire and Hopkins Symptoms Checklist-25 were written and subsequently validated in the Cambodian, Laotian, and Vietnamese languages. For use in a Dutch treatment center, with refugee patients mostly speaking other languages, additional translations were made. The objective of this study was examination of the psychometric properties of some of these new translations, i.e., the Arabic, Farsi, Serbo-Croatian, Russian, and English bilingual adaptations. It is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
179
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(187 citation statements)
references
References 6 publications
1
179
0
2
Order By: Relevance
“…The HSCL-25 includes a 15-item scale of depressive symptoms and the HTQ contains a 16-item scale of diagnostic criteria for PTSD as defined in the DSM-IV (APA, 1994). Both instruments have been widely translated and used in general studies among diverse cultural groups (Cardozo, Vergara, Agani & Gotway, 2000;Kagee, 2005;Mollica et al, 1999;Shrestha et al, 1998), including Cambodian populations (Dubois et al, 2004;Mollica et al, 1993), and have demonstrated high internal consistency and reliability across a range of population groups (Kleijn, Hovens & Rodenburg, 2001). Palmieri, Marshall and Schnell (2007) have conducted a confirmatory factor analysis study of the HTQ administrated in Khmer to resettled Cambodian refugees in a community study that demonstrated results similar to those found for English speakers completing other measures of PTSD symptom severity.…”
Section: Methodsmentioning
confidence: 99%
“…The HSCL-25 includes a 15-item scale of depressive symptoms and the HTQ contains a 16-item scale of diagnostic criteria for PTSD as defined in the DSM-IV (APA, 1994). Both instruments have been widely translated and used in general studies among diverse cultural groups (Cardozo, Vergara, Agani & Gotway, 2000;Kagee, 2005;Mollica et al, 1999;Shrestha et al, 1998), including Cambodian populations (Dubois et al, 2004;Mollica et al, 1993), and have demonstrated high internal consistency and reliability across a range of population groups (Kleijn, Hovens & Rodenburg, 2001). Palmieri, Marshall and Schnell (2007) have conducted a confirmatory factor analysis study of the HTQ administrated in Khmer to resettled Cambodian refugees in a community study that demonstrated results similar to those found for English speakers completing other measures of PTSD symptom severity.…”
Section: Methodsmentioning
confidence: 99%
“…22 The HTQ has demonstrated high internal consistency and reliability in studies of Bosnian-and Croatianspeaking individuals and in Cambodian refugee populations. [20][21][22][23] The HSCL-25, a screening tool to detect symptoms of anxiety and depression, comprises a 10-item subscale for anxiety and a 15-item subscale for depression. Mean cumulative symptom scores higher than 1.75 indicated the presence of anxiety and depression and have been found to be valid in predicting clinical diagnoses of these disorders.…”
Section: Instruments and Data Collectionmentioning
confidence: 99%
“…In addition, both instruments were translated into the most common languages spoken by refugees referred for treatment at Foundation Centrum ’45 (Arabic, Farsi, Serbo-Croatian, and Russian). Translations were carried out by certified translators or by bilingual staff members of Centrum ’45 and were reviewed by other certified translators (see Kleijn, Hovens, & Rodenburg, 2001). For the majority of individuals in each linguistic group, previously translated questionnaires could be used.…”
Section: Methodsmentioning
confidence: 99%